The directive principles for the phenomenon of the grammatical interpolation according to Abu Hayan Al Andalusi in Al Bahr Al Muhit - Al-Kaakati, Wassim Zakaria (Journal of Arabic Language Sciences and Literature, 2023)
The guidelines for the phenomenon of interpretation are comprehensive rules in their entirety, aiming to justify the grammatical guidelines for grammarians, so they are used to preponderate diacritical facets in a single case. These rules were described by Abu Hayyan with accurate definitions and prominent characteristics, including their coming in a consistent and integrated manner, so they were not contradictory in that some of them were negating the other, instead, Abu Hayyan often brought them to reinforce his negation of some of the grammatical facets that the previous grammarians mentioned, and he used to choose the closest meaning from others in the interpretations of Arabic syntax, and it follows grammatical rules away from far-fetched possibilities, and therefore we find him strict in interpreting some Khafd to be because it is neighboring a word that has Khafd, as well as negating interpretations based on “inclusion”, resorting in the first to inflective facets that he opines to be far from overexertion, and he sees that in the second matter, inclusion is only used when necessary; Because interpreting the word on its linguistic meaning takes precedence over inclusion. Likewise, he specified the interpretation to be based on delusion in the realm of conjunctions, and he did not deem it valid to use it in a comparative analogy because it is according to him a necessity and that is weak, and the necessity is not measured against it, instead, the interpretation is based on the language- even if it was a scarce usage- takes precedence over an interpretation based on delusion which is considered not valid to be used in a comparative analogy or odd.I have shown all this in my research and showed the rules and criteria adopted by Abu Hayyan, touching on the study of some of his examples contained in "The Bahr", adopting the analytical and inductive approaches.
Keywords: interpretation; rules; possibilities; inclusion; delusion